Growth performances and hemato-immunological responses of common carp (Cyprinus carpio Linnaeus, 1758) to fermented Aspergillus oryzae - S. A. Hedayati (2020)
© 2020 Iranian Fisheries Research Organization. All rights reserved. The present study investigates the effects of varying levels of dietary fermented Aspergillus oryzae (0 g Kg-1 as control group, 10, 20 and 30 g Kg-1) on performance and haemato-immunological indices of common carp (Cyprinus carpio) fingerlings. Common carp fingerlings (n=240, w=4.56±0.17 g) were supplied, randomly stocked in 12 aquaria and fed with experimental diets for 7 weeks. The results revealed no significant differences between performance parameters of fermented A. oryzae fed test and control diets (p>0.05). Also, evaluation of haematological parameters (RBC, Hct, Hb) and white blood cell (WBC) counts showed no notable changes between experimental groups (p>0.05). However, respiratory burst activity was meaningfully higher in fish fed fermented A. oryzae compared to control group (p<0.05). The present results showed that possible effects of administration of fermented A. oryzae on immune responses in carp fingerlings.